New Mediterranean Biodiversity Records (June 2012) - NICOLAIDOU, A.; ALONGI, G.; AYDOGAN, O.; CATRA, M.; CAVAS, L.; CEVIK, C.; DOSI, A.; CIRCOSTA, V.; GIAKOUMI, S.; GIMENEZ-CASALDUERO, F.; FILIZ, H.; IZQUIERDO-MUNOZ, A.; et al. (Mediterranean Marine Science, 2012)
The present work reports on the extended distribution of nineteen species in the Mediterranean. These are: Upeneus pori (Fish:Turkey), Bursatella leachii (Mollusca, Opisthobranchia: eastern coast of Spain), Sparisoma cretense (Fish: Ionian coast of Greece), Pseudobryopsis myura (Chlorophyta: Turkey), Aplysia dactylomela (Mollusca, Opisthobranchia: Karpathos island, and Kyklades Archipelago, Greece), Asparagopsis armata and Botryocladia madagascariensis (Rhodophyta: South Peloponnesos, Greece), Oxynotus centrina (Fish: Greece), Caulerpa racemosa var. cylindracea (Chlorophyta ), Stypopodium schimperi (Phaeophyta ) Siganus luridus and Stephanolepis diaspros (Fish) Percnon gibbesi (Decapoda, Brachyura) (Kyklades Archipelago, Greece), Cerithium scabridum (Mollusca, Prosobranchia: Anavissos: Greece) and Cerithium renovatum (Mollusca, Prosobranchia: N. Κriti), Cassiopea andromeda (Scyphomedusa: Rhodos Island, Greece), Abra tenuis (Mollusca Bivalvia: Vouliagmeni Lake, Greece) Lagocephalus lagocephalus (Fish: Calabrian coast, Italy) and Plocamopherus ocellatus (Mollusca, Opisthobranchia: İskenderun Bay, Turkey).